G50 An innovative approach to assessing nursing student's performance. (24th May 2017) - Corkin, D; Cardwell, P
Abstract : Aim: The desire and motivation to support the development of children's nursing students who thrive or may struggle in contemporary professional practice, is a key objective within pre-registration nurse education. Elemental factors of safety and quality in clinical practice have reinforced the need for rigorous, consistent and authentic assessment tools in order to test competency during programmes of education. Subsequently, the creation and development of final-year objective structured clinical examination (OSCE), aims to test the knowledge and skills of students in relation to their confidence, flexibility and approach to current practice demands, as they progress towards registrant status. Methods: Professional educators alongside clinical partners recognise the importance of this aim and the need to engage across educational and clinical boundaries, in developing such competency-based assessment tools (Zasadny & Bull, 2015). Two, 20 min, clinically-based scenarios were created, aimed at engaging students in performing an aspect of care delivery utilising the nursing process. Practice partners also contributed to this assessment process ensuring the authenticity of the experience and assessment activity. Realism in these activities was provided in the form of high-fidelity simulation manikins, simulated patients and carers. Data was collected and collated from examiners in these examinations, through the use of qualitative evaluation forms. Results: A total of 56 children's nursing students undertook this assessment in the final year of their programme, with a pass rate of 75.5% on first attempt. Overall, student feedback highlighted this assessment as challenging and stressful, not necessarily because of the skills being tested but their anxieties over being so closely observed and perceived expectations of staff. Clinical examiners noted many positive aspects of the student's performances, including professionalism, communication and child-centred care, alongside some challenges in effective infection control, prioritising needs and utilising assessment frameworks confidently. Nevertheless, examiners noted this new approach in utilising OSCE's as an evaluative tool to be a very worthwhile form of assessment. Conclusion: Utilising such an innovate approach to create an authentic assessment tool for children's field nursing students, has facilitated the opportunity to demonstrate safe, effective, autonomous practitioners during their educational journey.